Penyuluhan Kesehatan Deteksi Dini Tumbuh Kembang Mental Emosional Pada Anak - Eka Adithia Pratiwi; Istiana, Dian; Wasliah, Indah; Romadonika, Fitri (Insan Kreasi Media, 2023)
Growth and development are processes that occur in every human being, especially during childhood, this growth and development process occurs very quickly, especially in certain periods. The first five years are the period when the basic human personality is formed, sensing abilities, thinking, language and speaking skills, and social behavior. Each child's achievement of an ability can be different, but there are benchmarks for what development is carried out at each age stage. In order to reduce a child's growth and development problems, prevention must be carried out as early as possible. One of the problems that occurs in children today is that children's mental health problems are as important as their physical health problems. The method of implementing the activity is by providing health education related to children's mental and emotional problems, and training in early detection of children's mental and emotional problems. Results Monitoring and examining children's development regarding mental-emotional problems is important for parents to carry out. The pretest level of knowledge of parents in the poor category was 20 people (66.6%), the level of knowledge in the sufficient category was 5 people (16.7%), and the level of knowledge in the good category was 5 people (16.7). Meanwhile, the results of the post test showed that the level of knowledge of parents was in the sufficient category as many as 20 people (66.7%), and in the good category as many as 10 people (33.3%).